A Mendelian randomized study of circulating antioxidants in the diet and risk of cardiovascular disease - Ruonan Yang; Mingyue Lv; Xiujuan Yang; Siwei Zhai (Scientific Reports)
Abstract Cardiovascular diseases (CVD) are a major global mortality cause, heavily impacted by diet and oxidative stress. This study investigates the causal effects of five circulatory antioxidants on various cardiovascular diseases using Mendelian randomization (MR) to mitigate confounding biases.We conducted a two-sample Mendelian Randomization (MR) analysis utilizing summary-level genome-wide association study (GWAS) data from both the UK Biobank and FinnGen. Genetic instrumental variables for antioxidants, including vitamin A, beta-carotene, vitamin C, α-tocopherol, and lycopene, were identified based on rigorous criteria. The outcomes included arrhythmia, cardiomyopathy, heart failure, myocardial infarction, pericarditis, angina pectoris and coronary atherosclerosis.Higher genetically determined levels of α-tocopherol were associated with an increased risk of myocardial infarction (OR 5.10, 95% CI 2.92–8.91, P < 0.001) and cardiac arrhythmias (OR 1.94, 95% CI 1.34–2.83, P = 0.001). Retinol was linked to heightened risks of cardiomyopathy (OR 6.38, 95% CI 1.23–33.20, P = 0.028) and heart failure (OR 2.26, 95% CI 1.01–5.07, P = 0.047). A meta-analysis corroborated the pathogenic effects of α-carotene on arrhythmias (OR, 2.00; 95% CI, 1.39–2.86; P < 0.001) and myocardial infarction (OR, 4.81; 95% CI, 2.84–8.15; P < 0.001), α-tocopherol on angina pectoris (OR: 4.33; 95% CI: 2.07–9.09; P < 0.001) and coronary atherosclerosis (OR: 5.34; 95% CI: 2.81–10.12; P < 0.001).Our study indicates that elevated levels of specific antioxidants, particularly α-tocopherol and retinol, may increase the risk of certain cardiovascular diseases. Further research is necessary to clarify the impact of these antioxidants on cardiovascular health and to explore potential gene-environment interactions.